RNA-Seq Profiling of Serum Exosomal Circular RNAs Reveals Circ-PNN as a Potential Biomarker for Human Colorectal Cancer - Xie, Yan; Li, Juan; Li, Peilong; Li, Ning; Zhang, Ying; Binang, Helen; Zhao, Yinghui; Duan, Weili; Chen, Yingjie; Wang, Yunshan; Du, Lutao; Wang, Chuanxin (Frontiers in Oncology, 2020)
Circular RNAs (circRNAs) are an up-rising star in the non-coding RNA field. Growing evidences have revealed exosomal circular RNAs (circRNAs) as potential biomarkers for detection of various cancers. However, the clinical importance of most serum exosomal circRNAs in colorectal cancer (CRC) have rarely been investigated. In this study, we examined the possible clinical application of serum exosomal circRNAs in the diagnosis of CRC. Firstly, we conducted circular RNA microarray analysis using fifty CRC and fifty healthy control serum samples to identify CRC-related circRNAs. Then, eight most dysregulated circRNAs were selected for validation by reverse transcription quantitative polymerase chain reaction (RT-qPCR) assay. Receiver operating characteristic (ROC) curve analysis was performed to assess the diagnostic capability of one of the selected upregulated circRNAs (circ-PNN), and finally, a network map based on circ-PNN was constructed to determine its potential miRNA-mRNAs binding. The microarray data showed 122 differentially expressed circRNAs including 100 up-regulated and 22 down-regulated circRNA transcripts in CRC patients. Validation analysis revealed that the serum exosomal circ-PNN levels were significantly up-regulated in CRC cases compared with those in the control groups, which revealed similar findings with sequencing results. Moreover, serum exosomal circ-PNN level had good performance to distinguish CRC cases from healthy controls with an area under the ROC curve of 0.855 and 0.826 in the training and validation sets respectively, and the constructed network map based on circ-PNN provides potential candidates for future mechanism studies. Collectively, our findings indicated that serum exosomal circ-PNN might be a potential non-invasive biomarker for the early detection of CRC and may play a crucial role in the pathogenesis of CRC.